2015
DOI: 10.1128/mcb.00256-15
|View full text |Cite
|
Sign up to set email alerts
|

Transient Receptor Potential Channel 1 Deficiency Impairs Host Defense and Proinflammatory Responses to Bacterial Infection by Regulating Protein Kinase Cα Signaling

Abstract: dTransient receptor potential channel 1 (TRPC1) is a nonselective cation channel that is required for Ca 2؉ homeostasis necessary for cellular functions. However, whether TRPC1 is involved in infectious disease remains unknown. Here, we report a novel function for TRPC1 in host defense against Gram-negative bacteria. TRPC1؊/؊ mice exhibited decreased survival, severe lung injury, and systemic bacterial dissemination upon infection. Furthermore, silencing of TRPC1 showed decreased Ca 2؉ entry, reduced proinflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 45 publications
(57 reference statements)
0
32
0
Order By: Relevance
“…Macrophage-Mtb interactions reprogram various cellular, biochemical, and signaling events both in the host as well as the pathogen. 22 These reports suggest an important role of PLC signaling during bacterial interaction with host cells. 20 PLC signalling is involved in regulation of several cellular activities due to its ability to control the cellular levels of DAG and IP3.…”
Section: Discussionmentioning
confidence: 99%
“…Macrophage-Mtb interactions reprogram various cellular, biochemical, and signaling events both in the host as well as the pathogen. 22 These reports suggest an important role of PLC signaling during bacterial interaction with host cells. 20 PLC signalling is involved in regulation of several cellular activities due to its ability to control the cellular levels of DAG and IP3.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies have shown that silencing TRPC1 suppresses the JNK/NF-kB pathway during Gramnegative bacterial infection (19). However, TRPC1 function and its downstream signaling pathways have not been studied in HDM-induced allergic models.…”
Section: Hdm Challenge Induced Ca 2+ Influx Via the Trpc1 Channelmentioning
confidence: 99%
“…· decreased endothelial transmigration of neutrophils · decreased inflammatory response and ineffective bacterial clearance · no pulmonary hypertension response to chronic hypoxia and reduced vascular muscularisation Lindemann et al, 2015;Malczyk et al, 2013;Zhou et al, 2015 …”
Section: Trpc1 -/-mentioning
confidence: 99%
“…· reduced secretion of CCL2 (Sun et al, 2015) TRPML3 -/-· unknown www.ecmjournal.org been shown that ECM changes and hyperalgesia may correlate with dysregulation of TRP channels, suggesting that TRP channels are involved in sensing and regulating inflammation, mechanical and osmotic stress as well as pain in joints (Gavenis et al, 2009). Current knowledge on TRP channel expression and activity in nociceptors, chondrocytes and IVD cells is summarised below and in Fig.…”
Section: Trpml2 -/-mentioning
confidence: 99%